Unveiling the Dual Facet EFL Novice Teachers’ Identity Construction: Professionalism and Religious Identity - Kurniawati, Sri; Asih, Ria A.; Sudiran, Sudiran (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
Teacher’s identity is crucial for the development of a professional teacher in education. It evolves through a continuous process of refinement and adaptation. Nevertheless, the construction of novice teachers’ professional identity in Islamic Junior High Schools, especially in the Indonesian context, is under-explored. Thus, this study aims to explore the development of English teachers’ professional identities and the integration between such identities and Islamic values as their religious beliefs in teaching in Islamic Junior High Schools. The narrative inquiry method was employed by three novice English teachers in Jambi. The data was collected through in-depth interviews to explore the novice teachers’ stories. The results were analyzed using Miles’ model through data condensation, data display, and conclusions. The research results show that novice teachers’ professional identity construction began with several challenges regarding adapting to the new profession, developing diverse learners’ needs, adapting teaching methods, and performing assessments. In terms of religious identity, these novice teachers reported their abilities to integrate Islamic values into teaching English through the lesson materials, becoming role models, and embracing tolerance in a multicultural society. The findings of this study suggest the need for support for novice teachers, including mentorship programs and professional development workshops, to enhance their professionalism. Such endeavor is pivotal to supporting students’ spiritual and moral development, leading to more inclusive learning environments. Implications for future research are related to longitudinal studies tracking novice teachers’ development and exploring their coping strategies, focusing on one facet of teachers’ identity.